2014
DOI: 10.1186/1471-2350-15-9
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphisms and risk of diabetic nephropathy: a systematic review and meta-analysis

Abstract: BackgroundNitric oxide (NO) has numerous functions in the kidney, including control of renal and glomerular hemodynamics, by interfering at multiple pathological and physiologically critical steps of nephron function. Endothelial NOS (eNOS) gene has been considered a potential candidate gene to diabetic nephropathy (DN) susceptibility. Endothelial nitric oxide synthase gene (eNOS-3) polymorphisms have been associated with DN, however some studies do not confirm this association. The analyzed polymorphisms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 41 publications
(25 reference statements)
3
36
0
4
Order By: Relevance
“…Furthermore, asymmetric dimethyl arginine, an endogenous inhibitor of endothelial nitric oxide synthase (eNOS), is associated with the development and progression of diabetic nephropathy in patients (Lajer et al, 2008;Hanai et al, 2009;Shibata et al, 2009). Consistent with these studies, eNOS polymorphisms resulting in reduced enzyme expression or function have been associated with diabetic nephropathy (Dellamea et al, 2014). In an analysis of preclinical models of disease, it was demonstrated that deficiency of eNOS in db/db diabetic mice produced a renal gene expression profile that more closely resembled human diabetic nephropathy, compared with db/db mice with intact eNOS (Hodgin et al, 2013).…”
Section: Introductionsupporting
confidence: 51%
“…Furthermore, asymmetric dimethyl arginine, an endogenous inhibitor of endothelial nitric oxide synthase (eNOS), is associated with the development and progression of diabetic nephropathy in patients (Lajer et al, 2008;Hanai et al, 2009;Shibata et al, 2009). Consistent with these studies, eNOS polymorphisms resulting in reduced enzyme expression or function have been associated with diabetic nephropathy (Dellamea et al, 2014). In an analysis of preclinical models of disease, it was demonstrated that deficiency of eNOS in db/db diabetic mice produced a renal gene expression profile that more closely resembled human diabetic nephropathy, compared with db/db mice with intact eNOS (Hodgin et al, 2013).…”
Section: Introductionsupporting
confidence: 51%
“…9 Several studies have demonstrated that increased eNOS expression seems to be involved in the development and progression of DN. 10,11 Puerarin (daidzein-8-C-glucoside) is the main isoflavone isolated from the Chinese medicinal herb Ge-gen, the root of the wild leguminous creeper Pueraria lobata (kudzu root). 12 It has been shown effective in the treatment of kidney diseases, such as nephrotoxicity, acute kidney injury and nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…NO may play a role in insulin resistance and type 2 diabetes .NO is known to modulate the metabolism of glucose and hepatic and peripheral insulin secretion [13]. Indeed, endothelial dysfunction and decreased production of nitric oxide (NO) by endothelial NO synthase (eNOS) is involved in the pathogenesis of insulin resistance and hypertension [21].…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in CRP are associated with an increased risk for insulin resistance which contributes to endothelial dysfunction, predisposing the endothelium to a hyper inflammatory and thrombotic condition [13].…”
Section: Discussionmentioning
confidence: 99%